1999
DOI: 10.1016/s0956-053x(99)00148-8
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium removal from landfill leachate by chemical precipitation

Abstract:  the landfill leachate in Hong Kong usually contains quite high NH 4 + -N concentration, which is well known to inhibit nitrification in biological treatment processes. A common pre-treatment for reducing high strength of ammonium (NH 4 + -N) is by an air-stripping process. However, there are some operational problems such as carbonate scaling in the process of stripping. For this reason, some technical alternatives for NH 4 + -N removal from leachate need to be studied. In this study, a bench-scale experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
137
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(151 citation statements)
references
References 12 publications
9
137
0
5
Order By: Relevance
“…From Figure 2 (a), it was found that the mixed yeast strains grew at the maximum rate before 24 h when the concentration of (NH 4 ) 2 however, has often been reported. Anthonisen et al [1] found that methane-forming bacteria were inhibited in spite of pH control when the total ammonia was over 3000 mg I" 1 .…”
Section: Endurance Of Mixed Yeast To Ammoniamentioning
confidence: 97%
“…From Figure 2 (a), it was found that the mixed yeast strains grew at the maximum rate before 24 h when the concentration of (NH 4 ) 2 however, has often been reported. Anthonisen et al [1] found that methane-forming bacteria were inhibited in spite of pH control when the total ammonia was over 3000 mg I" 1 .…”
Section: Endurance Of Mixed Yeast To Ammoniamentioning
confidence: 97%
“…Generally, biological treatments such as aerobic, anaerobic, sequencing batch reactor, aerated lagoons, and activated sludge are effective in removing organic matters in the early stages (from young leachate) when the BOD 5 /COD ratio is greater than 0.4 (Kurniawan et al 2006;Renou et al 2008). On the contrary, biological treatment is inefficient when it comes to the treatment of stabilized leachate due to the narrow range of biodegradable components in leachate, the presence of substances toxic for the microorganism and the limited availability of necessary nutrients for microbial growth (Li et al 1999). Therefore, physico-chemical processes usually applied to treat persistent refractory compounds in stabilized leachate (Kamaruddin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While new biological techniques like short-cut nitrification/denitrification and anaerobic ammonium oxidization have demonstrated potential in solving the above problems, they are still under study and it is not yet possible to constantly control the nitrification process in the nitrite-formation dominating step Strous et al, 1997). Formation of magnesium ammonium phosphate (MAP), a crystal with a solubility as low as 0.0023 g per 100 ml H 2 O, has been considered to be an effective method for the removal of ammonium because of its high reaction rate and low residual ammonium concentration (Li et al, 1999). The method of MAP precipitation has been extensively studied to treat wastewater with high NH þ 4 content (Altinbas et al, 2002;Ozturk et al, 2003) of 1:1:1 for treating landfill leachate (Li and Zhao, 2001).…”
Section: Introductionmentioning
confidence: 99%